Music in ancient Greece and Rome - Landels, John G. (John Gray), 1926-2006 (Routledge, 2002)
Music in Ancient Greece and Rome provides a comprehensive introduction to the history of music from Homeric times to the Roman emperor Hadrian, presented in a concise and user-friendly way. Chapters include: * contexts in which music played a role * a detailed discussion of instruments * an analysis of scales, intervals and tuning * the principal types of rhythm used * and an exploration of Greek theories of harmony and acoustics. Music in Ancient Greece and Rome also contains numerous musical examples, with illustrations of ancient instruments.